KEWENANGAN PEMBUBARAN PARTAI POLITIK OLEH MAHKAMAH KONSTITUSI DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA (HAM) - Putu Eva Ditayani (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
This research examines the dissolution of political party by Constitutional Court, that becomes its authorities based on Article 24C UUDNRI 1945, from human right perspective. Indonesia as the state that implemented law of state of law acknowledge human rights as stated in the Constitution. Neverttheless, freedom of association as one of the principle of human rights as regulated in the Constitution, which used as the base of formation of a political party, can be ruled out and has limited implementation in which norms conflict arises. Limitation of freedom association is reflected in the sanction imposed by the Constitutional Court regarding dissolution of political party. The dissolution of political party by the Constitutional Court refers to certain regulation as Act No. 39 of 1999 that regulating Human Rights, Act No. 24 of 2003 that regulating The Constitutional Court, Act No. 2 of 2008 regulating Political Party, and The Constitutional Court Regulation governing the dissolution of a political party procedures by the Constutional Court. This research is a normative legal research that investigates the dissolution of a political party by the Constitutional Court that contrasts with formation of a political party as a representation of freedom of association, one of the human rights principle, without assessment on implementations or practices regarding those norms. According to descriptive analysis based on legal material regarding this issue, the limitation of freedom to associate can be performed based on Article 4 ICCPR 1966 because it can be considered as a right that its fulfillment can be limited by law. That dissolution by the Constitutional Court is not considered as violation of freedom to associate since the sanction only be imposed to violation of regulations by political parties. The purpose of limitation is only to protect the integrity of Republic of Indonesia and the discipline of the community, nation, and state members.